Rancang bangun prototype pnuematik untuk pengecekan tebal material - Adin; Alfian Saputra (Jurnal Teknik Mesin Indonesia, 2026)
Materials are crucial raw materials in the industrial world, both in terms of capacity, for both large and small industries. Over time, and with increasing competition, inspections are inextricably linked. Inspections require tools to simplify and increase measurement accuracy during operator operations. Automated systems utilizing pneumatics for inspection are increasingly used in the industrial world because they utilize readily available air. Tool design requires analysis, planning, and calculations of the required main components. The results of the planning process determine the pneumatic size based on the maximum load force and air pressure used, and can then determine the compressor power. In addition, pneumatic systems can be combined with conveyor systems, where the main conveyor design includes motor power, belt type, and roller shaft size, along with calculations for torque, speed, torsional moment, and bending moment.